KAJIAN KARAKTERISTIK ABNORMALITAS TANAMAN KELAPA SAWIT (Oil Palms) - Rahmawati, Aulia; Susanto, Ari (Jurnal Agroteknologi (Agronu), 2022)
Oil palm is the largest vegetable oil-producing plantation crop in the world. The need for oil palm seeds increases along with the increasing demand for oil palm products. The need for these seeds needs to be balanced with the presence of ordinary oil palm seeds. The abnormalities in oil palm plantations were found due to the selection of seeds that were less selective. Chimera in plants is the formation of characteristics that are governed by several genotypic constitutions and grow side by side with each other in tissues. In oil palm, chimeras can begin to appear in the seedling phase. The characteristics of abnormalities can be seen in terms of morphology and plant physiology. Based on morphological characteristics, chimera plants have a phenotype that is determined by the presence of white or bright yellow leaves parallel to the stem, stunted plants, rosettes, undeveloped leaves, mantle sissy flowers, followed by squirrel tail flowers (androgynous), thick coat fruits, and thin skin. . Based on physiological characteristics, chimeras occur due to changes in chloroplast development which result in changes in the chlorophyll content of oil palm plants. Oil palm plants that are considered abnormal from time to time can turn into normal plants depending on the level of abnormality of each plant. This study aims to examine the characteristics of abnormalities in oil palm plants. Therefore, it can be seen that oil palm seeds are classified as abnormal to be selected before planting in the field. This is done to obtain high potential oil palm plantations. Keywords : chimera, morphology, physiology, phenotype, genotype